Do healthcare providers consider the social determinants of health? Results from a nationwide cross-sectional study in the United States - Jeffrey Glenn; Gwen Kleinhenz; Jenna M.S. Smith; Robert A. Chaney; Victor B.A. Moxley; Paola G. Donoso Naranjo; Sarah Stone; Carl L. Hanson; Alisha H. Redelfs; M. Lelinneth B. Novilla (BMC, 2024)
Abstract Background While the social determinants of health (SDOH) have a greater impact on individual health outcomes than the healthcare services a person receives, healthcare providers face barriers to addressing these factors in clinical settings. Previous studies have shown that providers often lack the necessary knowledge and resources to adequately screen for and otherwise assist patients with unmet social needs. This study explores the perceptions and behaviors related to SDOH among healthcare providers in the United States (US). Methods This cross-sectional study analyzed data from a 22-item online survey using Reaction Data's research platform of healthcare professionals in the US. Survey items included demographic questions as well as Likert scale questions about healthcare providers' perceptions and behaviors related to SDOH. Descriptive statistics were calculated, and further analyses were conducted using t-tests and analysis of variance. Results A total of 563 respondents completed the survey, with the majority being male (72.6%), White (81%), and located in urban areas (82.2%). In terms of perceptions, most providers agreed or strongly agreed that SDOH affect the health outcomes of all patients (68.5%), while only 24.1% agreed or strongly agreed that their healthcare setting was set up to address SDOH. In terms of behavior, fewer than half currently screened for SDOH (48.6%) or addressed (42.7%) SDOH in other ways. Most providers (55.7%) wanted additional resources to focus on SDOH. Statistical analyses showed significant differences by gender, with females being more likely than males to prioritize SDOH, and by specialty, with psychiatrists, pediatricians, and family/general medicine practitioners being more likely to prioritize SDOH. Conclusion Most healthcare providers understand the connection between unmet social needs and their patients' health, but they also feel limited in their ability to address these issues. Ongoing efforts to improve medical education and shift the healthcare system to allow for payment and delivery of more holistic care that considers SDOH will likely provide new opportunities for healthcare providers. In addition to what they can do at the institutional and patient levels, providers have the potential to advocate for policy and system changes at the societal level that can better address the root causes of social issues.